1995
DOI: 10.1002/j.1460-2075.1995.tb07359.x
|View full text |Cite
|
Sign up to set email alerts
|

Protein-protein interaction via PAS domains: role of the PAS domain in positive and negative regulation of the bHLH/PAS dioxin receptor-Arnt transcription factor complex.

Abstract: Gene regulation by dioxins is mediated by the dioxin receptor‐Arnt heterodimer, a ligand generated complex of two basic helix‐loop‐helix (bHLH)/Per‐Arnt‐Sim (PAS) transcription factors. By using dioxin receptor chimeras where the dimerization and DNA binding bHLH motif has been replaced by a heterologous DNA binding domain, we have detected an ability of Arnt to interact with the dioxin receptor via the PAS domain in a mammalian ‘hybrid interaction’ system. By coimmunoprecipitation assays, we have confirmed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
140
0
4

Year Published

1997
1997
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(155 citation statements)
references
References 46 publications
11
140
0
4
Order By: Relevance
“…phosphorylation-deficient mutant phyA). Our data clearly showed that the phosphorylation of phyA influences the protein-protein interaction between phyA and its putative signal transducers, NDPK2 and PIF3, whose binding sites are near to the hinge region and to PER-ARNT-SIM-related domains implicated in mediating protein-protein interaction in other systems (Lindebro et al, 1995;Choi et al, 1999;Zhu et al, 2000). Another phytochrome-interacting protein, PKS1, which is known to bind the His kinase-related domain at the C-terminal end region , normally bound with phosphorylated phyA (data not shown).…”
Section: Discussionmentioning
confidence: 61%
“…phosphorylation-deficient mutant phyA). Our data clearly showed that the phosphorylation of phyA influences the protein-protein interaction between phyA and its putative signal transducers, NDPK2 and PIF3, whose binding sites are near to the hinge region and to PER-ARNT-SIM-related domains implicated in mediating protein-protein interaction in other systems (Lindebro et al, 1995;Choi et al, 1999;Zhu et al, 2000). Another phytochrome-interacting protein, PKS1, which is known to bind the His kinase-related domain at the C-terminal end region , normally bound with phosphorylated phyA (data not shown).…”
Section: Discussionmentioning
confidence: 61%
“…Empty pcDNA3.1 plasmid (Invitrogen) was used as a negative control for mock transfection. Plasmid containing full-length HIF-1β (pARNT/GEM7) was provided kindly by Prof. L. Poellinger, Karolinska Institute, Stockholm, Sweden [Lindebro et al, 1995]. Empty pCMV (Genlantis, San Diego, CA) vector was used as a negative control.…”
Section: Page 6 Of 30mentioning
confidence: 99%
“…We have previously demonstrated that the PAS domain of the dioxin receptor can function as a dimerization interface independently of the bHLH domain in a hybrid-protein interaction assay in mammalian cells (15). Furthermore, the C-terminal half of the PAS domain located between amino acids 230 and 421 and containing the minimal LBD spanning the PAS B motif has been shown to be essential for the PAS-mediated interaction with Arnt (15). We therefore examined the dimerization and DNA-binding activities of the dioxin receptor deletion mutant DR⌬PASB, lacking the minimal PAS B motif encompassed by amino acids 288 -421, but maintaining the N-terminal half of the LBD including the PAS A motif (Fig.…”
Section: Definition Of a Dioxin Receptor Deletion Mutant That Shows Bmentioning
confidence: 99%
“…Contiguous to the amino-terminal bHLH DNA-binding and dimerization motifs, members of this subfamily are identified on the basis of a second region of homology, the PAS (Per-Arnt-Sim) domain, originally identified in the Drosophila proteins PER and SIM, and Arnt. The PAS domain encompasses a region of ϳ250 -300 amino acids harboring two degenerate repeat sequences of 44 amino acids termed PAS A and PAS B, respectively, and has been shown to constitute an additional dimerization interface that can function independently of the bHLH motif (14,15). More recently, additional roles in the regulation of heterodimerization and DNA binding specificities have been attributed to the PAS domain (16,17).…”
mentioning
confidence: 99%